Quelques aspects de la transmission internationale de l’inflation - Rabeau, Yves (L'Actualité économique)

(untitled) (HEC Montréal, 1978)
In the first section, the impact of a shift in international demand on the price level of a small and open economy is analysed in the framework of the IS and LM diagram and under the assumption of a fixed exchange rate; only short run implications are derived from the analysis. In this keynesian context, it is shown, in particular, that the monetary policy implemented by a large country like the U.S. plays an important role in the assessment of the static short run impact of a change in international demand on the price level of a small country like Canada. In the second section of the paper, it is shown that a dynamic version of a keynesian macro model allows the rate of growth of prices of a small country to converge to the "international rate of inflation". In the last section, longer term issues are discussed in the context of the Scandinavian model of inflation. In particular, it is shown that a country like Canada with large regulated and para-public sectors is quite vulnerable to external inflationary shocks.